Peculiarities of the development of community-acquired pneumonia in certain population groups and the problem of choosing empirical antibacterial therapy - Kuanyshbaeva Dinara Rashidovna; Omarbaeva Zhumagaysha Toleuovna (European Research Materials, 2025)
Lower respiratory tract infections are the third leading cause of death in the world, second only to ischemic heart disease and cerebrovascular diseases, and in low-income countries they are the leading cause. According to the World Health Organization: more than three million deaths worldwide were registered in 2016 from lower respiratory tract infections, among which community-acquired pneumonia (CAP) occupies a leading place. Research in this area is actively conducted in almost all countries of the world. Consequently, CAP is a pressing problem of modern medicine and consists of a number of epidemiological, clinical, pharmacological and social aspects.